Research on the construction strategy of China’s rural emergency linkage system from the perspective of systems theory—based on the survey of six regions in China - Huang, Xinyang; Jiao, Yuning; Deng, Zihao; Wang, Tianyao; Hu, Yuyao; Liu, Yuting; Wang, Wei; Nie, Wei (Frontiers in Public Health, 2025)
PurposeThis study aims to understand the major challenges facing China’s rural pre-hospital emergency care in terms of coordination and cooperation. We focus particularly on the three-tier emergency care providers and their surrounding support units to explore the systematic and strategic gaps within the system. Based on these findings and general systems theory, we propose construction strategies for China’s rural emergency linkage system. This research provides new approaches for improving China’s overall rural emergency care capacity and offers reference points for rural emergency care development in other countries.MethodsWe visited 6 rural areas across 5 provinces and municipalities in China (Beijing, Shandong, Jiangsu, Zhejiang, and Jiangxi). We conducted semi-structured interviews with 28 grassroots emergency care personnel, including villagers with emergency care experience, village doctors, village officials, and emergency center staff. Through these interviews, we conducted in-depth research on the challenges facing rural emergency care coordination and gathered specific recommendations for improvement.ResultsIn current rural pre-hospital emergency care practice in China, coordination between different units remains insufficient, and the overall system development is still incomplete. The three-tier emergency care providers lack adequate information sharing, clear division of emergency responsibilities, and personnel exchange. Additionally, social and environmental factors such as funding limitations, compensation distribution issues, and rural transportation planning create barriers to rural emergency care development.ConclusionThe construction strategy for China’s rural emergency linkage system consists of two main components: the “emergency central system” and the “emergency peripheral system.” The central system focuses on integrating information sharing, medical care coordination, and human resources among emergency care providers. The peripheral system addresses economic support, road and address management, and strengthening emergency transportation capacity. Together, these systems can effectively enhance coordination within the emergency care system and improve the overall effectiveness of China’s rural emergency care.